Meeting Report: International Magnetosphere Coupling IV (IMC‐IV) Workshop GFZ‐Potsdam, Germany, 2–7 June 2024 - Julia Himmelsbach; Yuri Y. Shprits (Space Weather)
Abstract The International Magnetospheric Coupling (IMC‐IV) Workshop was held from 2–7 June 2024, at GFZ‐Potsdam, Germany and convened over 140 scientists to explore the solar wind and magnetosphere‐ionosphere‐thermosphere coupling. The workshop included eight sessions on topics ranging from solar wind, planetary magnetospheres, wave‐particle interactions to the ionosphere and upper atmosphere, and applications for space weather. Key subjects such as the need for advanced modeling, new satellite missions for validation, and the importance of understanding small and large‐scale space phenomena were emphasized by the participants. Two topical discussions focused on space weather awareness in Germany, and the future of Heliophysics research in Europe. The workshop concluded with recommendations for improved international mission coordination, better scientific communication, and enhanced public outreach through visualization tools. This meeting and the report pave the way for the formation of the European Heliophysics Community.